Crystal engineering in 3D: converting nanoscale lamellar manganese oxide to cubic spinel while affixed to a carbon architecture. Issue 32 (17th June 2016) - Donakowski, Martin D.; Wallace, Jean M.; Sassin, Megan B.; Chapman, Karena W.; Parker, Joseph F.; Long, Jeffrey W.; Rolison, Debra R.
Abstract : By applying differential pair distribution function analyses to MnO x -painted carbon nanofoam papers, we quantify the manganese oxide speciation as the nanoscale oxide transitions from disordered NaMnO x to spinel LiMn2 O4 . Abstract : By applying differential pair distribution function (DPDF) analyses to the energy-storage relevant MnO x /carbon system—but in a 3D architectural rather than powder-composite configuration—we can remove contributions of the carbon nanofoam paper scaffold and quantify the multiphasic oxide speciation as the nanoscale, disordered MnO x grafted to the carbon walls (MnO x @CNF) structurally rearranges in situ from disordered birnessite AMnO x (A = Na + ; Li + ) to tetragonal Mn3 O4 to spinel LiMn2 O4 . The first reaction step involves topotactic exchange of interlayer Na + by Li + in solution followed by thermal treatments to crystal engineer the ∼10 nm-thick 2D layered oxide throughout the macroscale nanofoam paper into a cubic phase. The oxide remains affixed to the walls of the nanofoam throughout the phase transformations. The DPDF fits are improved by retention of one plane of birnessite-like oxide after conversion to spinel. We support the DPDF-derived assignments by X-ray photoelectron spectroscopy and Raman spectroscopy, the latter of which tracks how crystal engineering the oxide affects the disorder of the carbon substrate. We further benchmark MnO x @CNF with nonaqueous electrochemical measurements versus lithium as the oxide converts from X-ray-amorphous birnessite to interlayer-registered LiMnO x to spinel. The lamellar AMnO x displays pseudocapacitive electrochemical behavior, with a doubling of specific capacitance for the interlayer-registered LiMnO x, while the spinel LiMn2 O4 @CNF displays a faradaic electrochemical response characteristic of Li-ion insertion. Our results highlight the need for holistic understanding when crystal engineering an (atomistic) charge-storing phase within the (architectural) structure of practical electrodes.